Impact of WTO an Indian Agricultural Prices - Shailza (Journal of Commerce and Trade, 2011)
Globalization, the part of economic reforms, initiated in India during 1991. World Trade Organization (WTO), the second generation of economic reforms has emerged as extended trend of globalization. Like other sectors, agriculture has also undergone many changes since 1995, after WTO. The developed countries have established WTO according their welfares and have made various loopholes in the Agreement on Agriculture (AOA) and allied agreements so that they may block the agricultural imports from developing countries. On the other hand, India has reduced tariffs and other restrictions during the last few years. Because of high level of export subsidy which is given through the Green Box and Blue Box under WTO in developed countries, Indian farmers have to sell their agricultural products at a low price to face the competition with cheap foreign products. We analyzed that the annual average inflation rate in agriculture decreased from 10.52% in pre WTO period to 5.34% in post WTO period. Thus, these data indicate that the growth rate of wholesale prices of agricultural products in India has decreased significantly during post WTO period.